Leadership Style on Employee Discipline at the Office of the Driving Teacher Center of South Sulawesi Province - Karmila, Cahya; Niswaty, Risma; Darwis, Muh; Suprianto, Suprianto (Journal of Public Policy and Local Government (JPPLG), 2024)
Employee discipline has a central role in maintaining organizational performance and achieving common goals. This research raises the issue of the influence of leadership style on employee discipline at the Office of the Driving Teacher Center (BBGP) of South Sulawesi Province. This research identifies how leadership style affects employee discipline, organizations can set more effective policies and programs to manage, train, and develop human resources. The research method used is quantitative by involving 62 respondents who are determined randomly through the Proportional Random Sampling Method. Data was collected through documentation and questionnaires and then analyzed using descriptive data analysis and inferential statistical analysis. The results of the study show that the Leadership Style variable (X) has an influence of 74.9% on the Employee Discipline variable (Y). This indicates that 74.9% of Employee Discipline is influenced by the Leadership Style factor. While the remaining 25.1% was influenced by other factors. This research strengthens the understanding of the importance of the role of leadership in shaping employee discipline in government organizations. These findings can be the basis for organizational management to pay more attention to leadership style as one of the key factors to improve employee discipline and overall organizational performance